2017
DOI: 10.3168/jds.2016-11528
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of volatile compounds in fermented milk using solid-phase microextraction methods coupled with gas chromatography-mass spectrometry

Abstract: Lactic acid bacteria (LAB) are industrially important bacteria that are widely used in the fermented food industry, especially in the manufacture of yogurt. Characteristic flavors are produced by LAB during fermentation and storage that affect the quality and acceptability of fermented milk products. In this study, the volatile compounds in milk fermented by Streptococcus thermophilus IMAU80842 alone, Lactobacillus delbrueckii ssp. bulgaricus IMAU20401 alone, or both species together were identified using soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
1
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 38 publications
4
90
1
15
Order By: Relevance
“…It has been previously reported that this compound may provide a unique aroma profile to fermented milks, since at low levels it gives aroma notes like bitter almonds and at high levels contributes to aroma notes like maraschino cherries [56]. This compound was also identified in other fermented milks [17,40). Other aldehydes such as 3-methyl-2-butenal and phenyl acetaldehyde were also detected in fermented milks.…”
Section: Identification and Chemical Groups Of Volatile Compoundsmentioning
confidence: 84%
See 2 more Smart Citations
“…It has been previously reported that this compound may provide a unique aroma profile to fermented milks, since at low levels it gives aroma notes like bitter almonds and at high levels contributes to aroma notes like maraschino cherries [56]. This compound was also identified in other fermented milks [17,40). Other aldehydes such as 3-methyl-2-butenal and phenyl acetaldehyde were also detected in fermented milks.…”
Section: Identification and Chemical Groups Of Volatile Compoundsmentioning
confidence: 84%
“…Acetic acid has been previously identified in unfermented milk samples [38,39] and in several fermented milks, such as a milk fermented with Lactobacillus pentosus (15), Lactobacillus casei DN-114 001 [38], Streptococcus thermophilus IMAU80842 and Lactobacillus delbrueckii ssp. bulgaricus IMAU20401 [40], Lactobacillus casei GBHM-21 [37], and Streptococcus thermophilus MGA45-4 [17].…”
Section: Identification and Chemical Groups Of Volatile Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Renz and Puhan (1975) concluded that bitterness in yogurt largely resulted from proteolysis by L. bulgaricus during storage. Dan et al (2017) used solidphase microextraction and gas chromatography-mass spectrometry methods to identify 53, 43, and 32 volatile compounds produced by S. thermophilus alone, L. bulgaricus alone, and both species together in fermented milk and confirmed the presence of some important flavor compounds including acetic acid, acetaldehyde, acetoin, 2,3-butanedione, ethanol, and 1-heptanol.…”
Section: Yogurt Cultures and Added Probioticsmentioning
confidence: 99%
“…Metabolomic techniques, including nuclear magnetic resonance (NMR) and mass spectrometry (MS), have been widely adopted in food science, nutrition and microbiology (Guertin et al, 2014;Pisano et al, 2016). Dan et al (2017) previously applied solid-phase microextraction coupled with gas chromatography (GC)-MS to identify the characteristic flavours produced by LAB during fermentation and storage and concluded that the composition of fermented milk volatile compounds was specific to the combination of LAB starters used (Dan et al, 2017). Moreover, the metabolic profile changed throughout the process of milk fermentation, and the metabolites including amino acids, organic acids, fatty acids and peptides differed among samples taken at different fermentation phases (Pan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%